Strengthening the Bendega Institution in Supporting Sustainable Development in Denpasar City - Putu Sri Widnyani, Ida Ayu; Githa Girindra, Ida Ayu; Sukma Eka Putri3, N. W. Ayu (Indonesian Association for Public Administration (IAPA), 2025)
Bendega is a traditional institution of Bali’s coastal communities that has an important role in marine governance, fisheries, and the preservation of maritime culture. However, modernization, tourism development, and urbanization in Denpasar City have posed challenges for the sustainability of Bendega’s function. This research aims to examine the existence of Bendega in Denpasar, identify the problems faced, and formulate a strategy to strengthen its institutions. The research uses a descriptive qualitative approach through literature studies, regulatory analysis, and interviews with Bendega figures and related stakeholders. The results of the study show that strengthening Bendega can be carried out through: (1) harmonization of regulations between local governments and customary rules, (2) institutional capacity building and member regeneration, (3) strengthening maritime-based economy, (4) revitalizing the value of Tri Hita Karana, and (5) multi-stakeholder collaboration. This study emphasizes the importance of strengthening Bendega as one of the foundations of sustainable development in the coastal area of Denpasar City.